Korean species of Gracillaria Haworth, 1828 (Lepidoptera: Gracillariidae) - Da-Som Kim; Ji-Young Lee; Bong-Kyu Byun (Journal of Asia-Pacific Biodiversity, 2022)
In this study, four species of the genus Gracillaria Haworth, 1828 (Lepidoptera: Gracillariidae), are recognized from Korea. Among them, two species, G. albicapitata Issiki, 1930 and G. arsenievi (Ermolaev, 1977), are reported for the first time from Korea. All the known species are enumerated with their available information. Adults and genitalia of all species are redescribed and illustrated.